(untitled) (The Pakistan Development Review, 2010)
It is my pleasure to welcome you all to the 26th Annual General Meeting and Conference of the PSDE. I would like to thank you Deputy Chairman and Past President of the PSDE for your time to inaugurate the meeting. I would like to thank our members and many guests who have come from all over Pakistan and abroad to participate in the Conference. A special welcome to students of economics and business studies from PIDE and different universities in Islamabad and from different parts of Pakistan, who are I am sure, just as eager as the senior members to understand the issues to be discussed at the Conference better. Let me join Dr Musleh ud Din in welcoming our distinguished speakers, Dr Vito Tanzi, Dr Ehtisham Ahmed and Dr Anwar Shah who will be delivering the invited lectures this year. Our chief guest, I might add at short notice, will deliver the prestigious Quaid-i-Azam Lecture this year.